Identification, characterization, and expression profiling of the putative U-box E3 ubiquitin ligase gene family in Sorghum bicolor - Fang, Yuanpeng; Du, Qiaoli; Yang, Qian; Jiang, Junmei; Hou, Xiaolong; Yang, Zaifu; Zhao, Degang; Li, Xiangyang; Xie, Xin (Frontiers in Microbiology, 2022)
The U-box family is one of the main E3 ubiquitin ligase families in plants. The U-box family has been characterized in several species. However, genome-wide gene identification and expression profiling of the U-box family in response to abiotic stress in Sorghum bicolor remain unclear. In this study, we broadly identified 68 U-box genes in the sorghum genome, including 2 CHIP genes, and 1 typical UFD2 (Ub fusion degradation 2) gene. The U-box gene family was divided into eight subclasses based on homology and conserved domain characteristics. Evolutionary analysis identified 14, 66, and 82 U-box collinear gene pairs in sorghum compared with arabidopsis, rice, and maize, respectively, and a unique tandem repeat pair (SbPUB26/SbPUB27) is present in the sorghum genome. Gene Ontology (GO) enrichment analysis showed that U-box proteins were mainly related to ubiquitination and modification, and various stress responses. Comprehensive analysis of promoters, expression profiling, and gene co-regulation networks also revealed that many sorghum U-box genes may be correlated with multiple stress responses. In summary, our results showed that sorghum contains 68 U-box genes, which may be involved in multiple abiotic stress responses. The findings will support future gene functional studies related to ubiquitination in sorghum.